New species of Bryophaenocladius Thienemann, 1934 (Diptera: Chironomidae) from Argentina - Donato, Mariano; Mauad, Melina; Siri, Augusto (Zootaxa, 2024)
Three new species of Bryophaenocladius Thienemann are described and figured as male imagines: B. urbanus sp. n. from Central Argentina, and B. virgotruncatus sp. n. and B. nasus sp. n. from Argentinean Patagonia. A geometric morphometric analysis was performed to evaluate the taxonomic value of the shape of the anal point in species delimitation. The analysis involved 96 species. As a result, the Bryophaenocladius species showed significant anal point patterns of shape change, recovering three main shape types: rounded, equilateral triangle-shaped, and isosceles triangle-shaped. An identification key of the Bryophaenocladius species from the Neotropical region is provided.